Daily Objective Physical Activity and Sedentary Time in Adults with COPD Using Spirometry Data from Canadian Measures Health Survey - P. Bernard; G. Hains-Monfette; S. Atoui; G. Moullec (Canadian Respiratory Journal)
Chronic obstructive pulmonary disease (COPD) is expected to be the third leading cause of premature death and disability in Canada and around the world by the year 2020. The study aims to compare objective physical activity (PA) and sedentary time in a population-based sample of adults with chronic obstructive pulmonary disease (COPD) and compare a group, and to investigate whether these behaviors differ according to COPD severity. From the 2007–2013 Canadian Health Measures Survey dataset, accelerometer and prebronchodilator spirometry data were available for 6441 participants, aged 35 to 79. Two weighted analyses of covariance were performed with adjustments for age, sex, body mass index, accelerometer wearing time, season, work, smoking (cotinine), education level, and income. A set of sensitivity analyses were carried out to examine the possible effect of COPD and type of control group. A cross-sectional weighted analysis indicated that 14.6% of study participants had a measured airflow obstruction consistent with COPD. Time in PA (moderate-vigorous and light PA), number of steps, and sedentary duration were not significantly different in participants with COPD, taken together, compared to controls. However, moderate to severe COPD participants (stages ≥2) had a significantly lower daily time spent in PA of moderate and vigorous intensity level compared to controls. Canadian adults with COPD with all disease severity levels combined did not show lower daily duration of light, moderate, and vigorous PA, and number of steps and higher daily sedentary time than those without airflow obstruction. Both groups are extremely sedentary and have low PA duration. Thus, “move more and sit less” public health strategy could equally target adults with or without COPD.